ANTI-TRYPANOSOMAL ACTIVITY OF THE ETHANOLIC EXTRACT OF BUCHHOLZIA CORIACEA SEEDS - Nweze, N. E.; Fakae, L. B.; Asuzu, I. U. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The seeds of Buchholzia coriacea Engler (Capparaceae) are folklorically used in Eastern Nigeria, to treat feverish conditions. The seeds are commonly called wonderful colas. They are chopped up and soaked overnight in the local gin. The infusion is drunk for the cure of such ailments as malaria in humans. Malaria and animal trypanosomiasis are two important protozoan diseases which are endemic in Nigeria. The crude ethanolic extract of Buchholzia coriacea seeds was evaluated for anti-trypanosomal activity in mice experimentally infected with Trypanosoma brucei brucei. Parasitaemia was monitored using the rapid matching technique as well as the microscopic examination of the buffy coat. Packed cell volume of the bIood was monitored using the microhaematocrit tube. In the acute toxicity test no deaths were recorded. Signs of dizziness were observed at 2000 mg/kg/ip. The extract reduced the number of trypanosomes in the blood. The reduction was dose dependent. At 1000 mg/kg there was a complete clearance of the trypanosomes in the blood 13 days post-infection (PI) and after 3 days of consecutive treatment. Treatment was stopped and by the 15th day PI there was a relapse of infection. Reductions in packed cell volumes (PCV) followed infection. But as treatment was instituted, increase in PCV was observed. The increase was dose-dependent and may have resulted from the effect of treatment as there was a concurrent reduction in parasitaemia. This finding suggests that the ethanolic extract of Buchholzia coriacea seed has anti – trypanosomal activity in mice experimentally infected with T. brucei brucei.